2012
DOI: 10.1016/j.atmosenv.2012.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Intra-urban spatial variability of PM2.5-bound carbonaceous components

Abstract: The Denver Aerosol Sources and Health (DASH) study was designed to evaluate associations between PM2.5 species and sources and adverse human health effects. The DASH study generated a five-year (2003–2007) time series of daily speciated PM2.5 concentration measurements from a single, special-purpose monitoring site in Denver, CO. To evaluate the ability of this site to adequately represent the short term temporal variability of PM2.5 concentrations in the five county Denver metropolitan area, a one year supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…However, gasoline versus diesel vehicle contributions to these heavy PAHs could not be separated in this work, likely due to their similar emission factors (Phuleria et al, 2007). In a separate paper, Xie et al (in press) presented a ratio-ratio plot comparing indeno[1,2,3-cd]pyrene and benzo[ghi]perylene normalized by EC, which also suggested that gasoline and diesel were both significant sources.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, gasoline versus diesel vehicle contributions to these heavy PAHs could not be separated in this work, likely due to their similar emission factors (Phuleria et al, 2007). In a separate paper, Xie et al (in press) presented a ratio-ratio plot comparing indeno[1,2,3-cd]pyrene and benzo[ghi]perylene normalized by EC, which also suggested that gasoline and diesel were both significant sources.…”
Section: Resultsmentioning
confidence: 99%
“…This association is supported by observation that EC concentrations show a greater proportional reduction on the weekend than that in overall traffic counts (Dutton et al, 2010a). In ratio-ratio plots, the ambient sterane data at the four sites were mostly explained by a continuum of gasoline vehicle source profiles, and partially ascribed to light duty diesel vehicles (Xie et al, in press). As a result, this sterane/EC factor was categorized as lubricating oil combustion, which is also obtained by Dutton et al, (2010b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations